Teacher’s Challenges towards Online Learning in Pandemic Era - Elsa Rosalina; Nasrullah Nasrullah; Eka Puteri Elyani (LET: Linguistics, Literature and English Teaching Journal, 2020)
The teaching and learning process has a big revolution since Corona Virus Disease 19 (COVID19) has spread out to the world. Education is one of the sectors that have a mostly big impact on its condition. COVID 19 changes everything in the education system. The teaching and learning process which do face to face must be changed to an online system. Thus, in this research, the researchers want to identify the teacher’s challenges for doing online teaching and learning. The researchers also describe the strength and weaknesses of online learning based on teachers’ perceptions. This research used a qualitative approach because the researchers describe teacher challenges toward online learning and the easiness and the difficulties of online learning in the pandemic era. The participants of this research were 14 English teachers from a different level of education in South Kalimantan. The instruments used in this study consisted of 12 open-ended questionnaires made online using Google form. The result of the questionnaire that has filled out by the participants recorded in the researcher’s email, then based on this result the researchers describe the findings and related it to the relevant theory. The findings of this research are most of the teachers agree that the challenges to applying online learning are in facilitation such as internet connection, quota, the places of home living, and the process of online learning itself such as the teacher’s less in technology for designing interesting online learning activities, less communicative, lack of interaction, and fostering an effective online learning climate and for the strength and the weakness of online learning activities most of the teachers agree that the strength of online learning is flexible in time and place, thus the teaching and learning can conduct everywhere and anytime, for the weakness the teacher agree that online learning can’t conduct maximal pedagogy process in learning activities.  Keywords: teacher, challenges, online learning, pandemic era